Facilitators and barriers of healthcare workers’ recommendation of HPV vaccine for adolescents in Nigeria: views through the lens of theoretical domains framework (2022)
Background: The human Papillomavirus (HPV) vaccine has demonstrated efficacy in the prevention of cervical cancer when given in early adolescence. The recommendation of the vaccine by health care workers (HCW) is crucial to the uptake of the vaccine by adolescents and the process of this recommendation is important as it determines subsequent uptake of the vaccine. Understanding of the facilitators and barriers of recommendation of this vaccine can help in the development of strategies to improve its recommendation rates and uptake. This study therefore explored the facilitators and barriers for the recommendation of HPV vaccine for adolescents by HCW in Ibadan, Nigeria using the Theoretical Domain Framework (TDF). Methods: Key informant interviews were conducted with 14 purposively selected HCW who were in charge of vaccination. Content analysis was used after deductive coding of the data using the domains of the TDF. Relevant concepts for facilitators and barriers of HPV vaccine recommendation and quotes were then identified. Results: Mean age of the HCW was 47.7 ± 6.5 years and they consisted of eight nurses, four medical doctors, one medical social worker and one health visitor. Ten domains of the TDF were represented among the facilitators and barriers against the recommendation of HPV vaccination by the HCW, except the goals; memory, attention, decision process; emotion; and behavioral regulation domains. The domains with the highest frequency of concepts were: knowledge, skills, social/professional role and identity, beliefs about capabilities, beliefs about consequences, intention and environmental context and resources. Domains with conflicting statements in the concept were: environmental context and resources, and beliefs about consequences. While those with perceived strength of concept were: social influences, reinforcement and optimism. Conclusion: All the 10 identified domains of the TDF are potential areas of focus for strategies for improving the recommendation of HPV vaccine for adolescents by health care workers in Nigeria and other countries with similar sociocultural settings.